2006
DOI: 10.1021/jp055150g
|View full text |Cite
|
Sign up to set email alerts
|

O2 Reduction on Graphite and Nitrogen-Doped Graphite:  Experiment and Theory

Abstract: An experimental and theoretical study of electroreduction of oxygen to hydrogen peroxide is presented. The experimental measurements of nitrided Ketjenblack indicated an onset potential for reduction of approximately 0.5 V (SHE) compared to the onset potential of 0.2 V observed for untreated carbon. Quantum calculations on cluster models of nitrided and un-nitrided graphite sheets show that carbon radical sites formed adjacent to substitutional N in graphite are active for O 2 electroreduction to H 2 O 2 via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
491
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 609 publications
(518 citation statements)
references
References 27 publications
19
491
0
8
Order By: Relevance
“…It is normally believed that pyridinic N doped at the edge of the graphitic layers is effective for ORR as such N-doping can reduce the energy barrier for oxygen adsorption on adjacent carbon atoms, and accelerate the rate-limiting firstelectron transfer during the ORR 20 . Quantum theory calculation and previous experimental results also suggested that doping of quaternary N into graphene planes could induce a non-uniform electron distribution and short C-N bonds, comparable to O-O bonds, which would facilitate O 2 adsorption and subsequent disassociation/weakening of O ¼ O bonds 19,21 .…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…It is normally believed that pyridinic N doped at the edge of the graphitic layers is effective for ORR as such N-doping can reduce the energy barrier for oxygen adsorption on adjacent carbon atoms, and accelerate the rate-limiting firstelectron transfer during the ORR 20 . Quantum theory calculation and previous experimental results also suggested that doping of quaternary N into graphene planes could induce a non-uniform electron distribution and short C-N bonds, comparable to O-O bonds, which would facilitate O 2 adsorption and subsequent disassociation/weakening of O ¼ O bonds 19,21 .…”
Section: Resultsmentioning
confidence: 77%
“…This can be explained by the reactions between NH 3 and oxygen functionalities located on the carbon surface, possibly resulting in new nitrogen-containing active sites 12,29 . Surprisingly, the final nitrogen content of meso/micro-PoPD (3.15 at%) obtained with NH 3 activation was significantly lower than that of meso-PoPD (9.5 at%), although NH 3 was generally recognized as a nitrogen precursor for preparing N-doped carbon catalysts [10][11][12]18,19 . We reason that, besides the surface reaction with oxygen species, NH 3 molecules can also react with the carbon matrix under high temperature, preferably with disordered carbon phases [30][31][32] .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The performance is effected dramatically by the MFC design,1 operating temperature,74 altitude above sea level, electrolyte utilized (different solution conductivity),43 bacteria utilized (e.g., single or mixed culture),1 organic compounds utilized (e.g., lactate, acetate, fumarate, etc. ),3, 75 organics concentration,74 and the presence or absence of membranes 66. Several other studies demonstrated the utilization of Fe‐based catalysts with excellent performances and superiority over platinum‐based cathodes22, 23 or AC‐based cathodes 43…”
Section: Resultsmentioning
confidence: 98%
“…Nitrogen has been identified to have a positive effect on the ORR owing to its ability to improve the electronic properties 64, 65, 66. However, excess nitrogen concentrations may be harmful to the overall performance, as it decreases the conductivity of the material.…”
Section: Resultsmentioning
confidence: 99%